The effects of caregiver and household HIV on child development: a community‐based longitudinal study of young children. (11th August 2016) - Sherr, L.; Skeen, S.; Hensels, I. S.; Tomlinson, M.; Macedo, A.
Abstract: Objective: Many studies that document child outcomes in the context of parental HIV – which has been established as a risk factor for child development – focus on older children/adolescents. Studies also concentrate on the status of the primary caregiver, not other household members who might be infected. Design: This study examined the effects of caregiver and household HIV on child development (4–13 years) in South Africa and Malawi (2011–2014). Methods: Data were gathered from 989 children and their primary caregivers at baseline and repeated at 12–15 months follow‐up (86.5% follow‐up rate). Only caregivers of a single child and caregiver/child dyads without missing data were included, providing a sample of 808 dyads for analysis. Children were divided into three groups according to caregiver‐reported HIV burden: having an HIV‐positive primary caregiver (19.8%), having HIV in the household (14.2%) or no HIV (66%). Results: The HIV burden was positively associated with an array of negative child outcomes, often mediated by caregiver depression levels. Family HIV burden at baseline affected child behavioural problems at follow‐up indirectly through carer depression ( B = 0.02; CI = 0.003, 0.06). Internalizing ( B = 0.02; CI = 0.002, 0.05) and externalizing problems at follow‐up ( B = 0.01; CI = 0.0002, 0.03) were also indirectly affected by family HIV burden through caregiver depression. Conclusions: The data suggest that family HIV can affect child development, emphasizing the important role of depression in the pathway to such an effect. Community‐based interventions directed at alleviating parental depression in the presence of HIV may help to interrupt the cycle of family HIV and adverse child outcomes.